The Influence of Creativity, Product Innovation, and Marketing Strategy on Increasing Consumer Purchasing Power PT. Kaya Ilmu Bermanfaat - Tina Amelia; Roma Nova Cahjati Poetry (PT Publikasiku Academic Solution, 2024)
This research aims to analyze the influence of the variables of creativity, product innovation, and marketing strategy on increasing the purchasing power of PT Kaya Ilmu Bermanfaat consumers. This research uses survey research, where research data is obtained from questionnaires distributed to respondents and is generally carried out by testing hypotheses. Research is conducted on PT. Kaya Ilmu Bermanfaat. The research approach used is a quantitative approach, where this research approach is carried out directly in the field, from the data obtained, then the researcher will carry out hypothesis testing using statistical analysis The population are consumers of PT Kaya Ilmu Bermanfaat. The sampling method used was nonprobability sampling with a purposive sampling technique so that a research sample of 100 respondents was obtained. The data analysis technique used is PLS-SEM. The research results show that creativity and innovation have a positive and insignificant effect on increasing consumer purchasing power partially. Meanwhile, marketing strategy has a positive and significant effect on increasing consumer purchasing power.